A new species of Oreodera Audinet-Serville, 1835 from Ecuador (Coleoptera, Cerambycidae, Lamiinae) and new geographical records - Santos-Silva, Antonio; Botero, Juan Pablo (Zootaxa, 2016)
Oreodera antonkozlovi, new species from Ecuador is described and illustrated. A key to species of Oreodera, currently known from Ecuador, is provided. Moreover, the following new country records are reported in Oreodera: O. basicretata (Brazil); O. cretata (Peru); O. sororcula (Brazil); O. wappesi (Costa Rica and Guatemala). Additionally, new state records from Brazil are added: O. bituberculata (Goiás); O. griseozonata (Amapá); O. melzeri (Amazonas).